A new approach for minimum phase output definition. Issue 2 (25th January 2017) - Jahangiri, Fatemeh; Talebi, Heidar Ali; Menhaj, Mohammad Bagher; Ebenbauer, Christian
ABSTRACT: This paper presents a novel method for output redefinition for linear systems. The approach also determines possible relative degrees for the systems corresponding to any new output vector. To guarantee the minimum phase property with a prescribed relative degree, a set of new conditions is introduced. A key feature of these conditions is that there is no need to any form of transformations which make the scheme suitable for optimisation problems in control to ensure the minimum phase property. Moreover, the results are useful for sensor placement problems and for obtaining minimum phase approximations of non-minimum phase systems. Numerical examples including an example of unmanned aerial vehicle systems are given to demonstrate the effectiveness of the methodology.